(untitled) (Phenomenology, Humanities and Sciences, 2022)
The article presents the criticism developed by Gurwitsch of Husserl’s phenomeno-logy of perception and the revision of the theory of intentionality that follows from it. We begin with the positive appreciation of Husserl’s conception of consciousness in terms of intentiona-lity, which, according to Gurwitsch, is the only conception capable of solving the problem of consciousness of the identity of the object, which is rooted in British empiricism. Next, we will see that Gurwitsch still understands this conception, despite its merits, as reminiscent of the constancy hypothesis, which motivates him to revise its theoretical foundations to safeguard it from this weak point. This revision focuses on the elimination of the concept of formless sensible hylé. This elimination is made possible through the concept of internal horizon. It is concluded that the revision of the theory of intentionality starting with the elimination of the concept of sensible hylé: 1) does not contradict Gurwitsch’s initial appreciation of Husserlian theory as revolutionary and as the only one to solve the “problem of consciousness” and 2) lays the foundations for the development of his own Gestalt theory.